2022
DOI: 10.1186/s12893-022-01622-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term postoperative outcomes of Roux-en-Y cholangiojejunostomy in patients with benign biliary stricture

Abstract: Background Although there are common postoperative complications, Roux-en-Y cholangiojejunostomy is still broadly used as a standard surgical procedure for patients with biliary stricture. This study aimed to explore long-term risk factors of cholangiojejunostomy in patients with biliary stricture who underwent revisional cholangiojejunostomy. Methods Clinical data of 61 patients with biliary stricture undergoing revisional cholangiojejunostomy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Postoperative biliary fistula, fluid accumulation in the operation area, bile duct infection, biliary bleeding, biliary stricture, etc. are common complications, which are related to the hospital stay, survival period and long-term prognosis of patients [ 17 ]. Secondly, the body damage of patients with biliary stricture is long-term and persistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative biliary fistula, fluid accumulation in the operation area, bile duct infection, biliary bleeding, biliary stricture, etc. are common complications, which are related to the hospital stay, survival period and long-term prognosis of patients [ 17 ]. Secondly, the body damage of patients with biliary stricture is long-term and persistent.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of imaging manifestations, magnetic resonance cholangiopancreatography (MRCP), computed tomography (CT), B-ultrasound, T-tube radiography, choledochoscopy, duodenoscopy and other imaging examinations and endoscopy have played an important role in the diagnosis and differential diagnosis of postoperative biliary stenosis [8][9][10]. Due to the persistence of stenosis, secondary surgery under endoscopy, direct vision or endoscopy is often required, which not only increases the pain of patients, but also wastes medical resources [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extensive research has consistently revealed that chronic inflammatory stimuli can give rise to various detrimental health outcomes, such as anastomosis stenosis, stone formation, and an increased risk of cancer development. 6,7 Preserving the sphincter of Oddi as much as possible to prevent reflux is considered an optimal treatment approach for benign strictures. Therefore, repairing with patches for small injuries and replacing the entire bile duct for large injuries are the easiest and most ideal treatment methods for this problem, which also represents the necessity of biliary surgery research on artificial bile ducts.…”
Section: Introductionmentioning
confidence: 99%